Writing architectures : ficto-critical approaches - Frichot, Hélène; Stead, Naomi (Bloomsbury Visual Arts, 2020)
Architects and fiction writers share the same ambition: to imagine new worlds into being. Every architectural proposition is a kind of fiction before it becomes a built fact; likewise, every written fiction relies on the construction of a context in which a story can take place. This collection of essays explores what happens when fiction, experimental writing and criticism are combined and applied to architectural projects and problems. It begins with ficto-criticism -- an experimental and often feminist mode of writing which fuses the forms and genres of essay, critique, and story -- and extends it into the domain of architecture, challenging assumptions about our contemporary social and political realities, and placing architecture in contact with such disciplines as cultural studies, literary theory and ethnography. These sixteen newly-written pieces have been selected for this volume to show how ficto-critical writing can be a powerful vehicle for creative architectural practice, providing new opportunities to explore modes of writing about architecture both within and beyond the discipline. The collection represents a broad range of geographical and cultural positions including indigenous and non-Western contexts, and includes a foreword and afterword by important thinkers in the domains of architectural criticism (Jane Rendell) and cultural studies/ethnography (Stephen Muecke).
Keywords: Architectural criticism.; Critical discourse analysis.; Literature -- Aesthetics.; Critique d'architecture.; Analyse critique du discours.; Littérature -- Esthétique.; architectural criticism.; Theory of architecture.; Architectural criticism; Critical discourse analysis; Literature -- Aesthetics